Clinical outcome after air-assisted manual deep anterior lamellar keratoplasty for fungal keratitis poorly responsive to medical treatment - Uchio E (Dove Medical Press, 2019)
Eiichi Uchio,1 Yusuke Saeki,1 Tomoko Tsukahara-Kawamura,1 Kazuaki Kadonosono,2 Hiroaki Ozaki1 1Department of Ophthalmology, Fukuoka University School of Medicine, Fukuoka, Japan; 2Department of Ophthalmology, Yokohama City University Medical Center, Yokohama, JapanCorrespondence: Eiichi UchioDepartment of Ophthalmology, Fukuoka University School of Medicine, 7-45-1 Nanakuma, Jonan-ku, Fukuoka 814-0180, JapanTel +81 92 801 1011Fax +81 92 865 4445Email euchio@fukuoka-u.ac.jpPurpose: Fungal keratitis remains an important disorder because of difficulty in its diagnosis, and some patients do not respond to medical treatment using antifungal local and systemic agents. This study was carried out to determine the therapeutic value of air-assisted manual therapeutic deep anterior lamellar keratoplasty (TDALK) in the treatment of fungal keratitis not curable by antifungal chemotherapy.Methods: Seventeen patients (18 eyes) who were referred to Fukuoka University Hospital and treated surgically from January 2006 to April 2018, in whom a diagnosis of fungal keratitis was confirmed by typical clinical findings and microbiological or histological analysis of corneal specimens, and who were poorly responsive to topical and systemic antifungal medication, whereas the lesion had not resulted in corneal perforation, were enrolled in this study and were treated by air-assisted manual TDALK. Clinical outcomes including treatment course, therapeutic success rate, visual acuity outcomes and graft clarity rate were analyzed.Results: The most common pathogen was Fusarium, followed by Candida and Aspergillus. Beneficial therapeutic results (a clear or translucent graft) were achieved in 15 of 18 eyes (83%). There was no recurrence of infection and resulting visual acuity ≤0.15 logarithm of minimal angle of resolution unit was achieved in 15 eyes (83%). Intraoperative microperforation of Descemet’s membrane (DM) was not observed in any patients.Conclusion: Air-assisted manual TDALK can be effective for treating severe fungal keratitis. In addition, air-assisted manual TDALK might be an alternative procedure to big-bubble DALK, because it can provide ambulatory vision and can preserve potentiality of vision with less risk of intraoperative perforation of DM.Keywords: fungal keratitis, lamellar keratoplasty, fusarium, candida, therapeutic keratoplasty